Congrong Shujing Granules ameliorates mitochondrial associated membranes to against MPP+-induced neurological damage in the cellular model of Parkinson’s disease - Chutian Zhang; Chutian Zhang; Peizhen Huang; Huiling Cheng; Xinxin Yuan; Mei Zhou; Ying Liu; Ting Liu; Dan Chen; Qian Xu; Jing Cai; Jing Cai (Frontiers in Pharmacology)
ContextCongrong-Shujing Granules (CRSJG) are known to protect dopaminergic neurons in Parkinson’s disease (PD), and the mechanism may be related to the improvement of mitochondria-associated membranes (MAMs).ObjectiveTo investigate the impact of CRSJG-medicated serum on MAMs in the 1-methyl-4-phenylpyridinium (MPP+)-induced PD cell model.Materials and methodsHuman neuroblastoma (SH-SY5Y) cells were treated with 1,000 μmol/L MPP+ for 24 h, resulting in three experimental groups: MPP+, CRSJG, and 2-APB. The MPP+ group received blank serum, CRSJG group was treated with CRSJG-medicated serum, and the 2-APB group was given 100 μmol/L 2-APB. An untreated control group was also included. Serum pharmacokinetics for the CRSJG group were analyzed using ultra-performance liquid chromatography-tandem mass spectrometry. Intracellular-Ca2+, reactive oxygen species (ROS), mitochondrial membrane potential (MMP), and apoptosis rates were measured using fluorescent probes and flow cytometry. Transmission electron microscopy was employed to examine the morphology of MAMs. Western blot was conducted to identify proteins related to apoptosis and Ca2+ transport.ResultsCRSJG-medicated serum identified by pharmacokinetic markers including echinacoside, paeoniflorin, salvianolic acid B, acteoside, and tanshinone IIa. The EC50 for MPP+-induced reduction in cell proliferation was 1,110 μmol/L. CRSJG-medicated serum, especially at 2.5%, significantly improved cell proliferation after 24 h. The serum effectively mitigated damage within the MAMs region and reduced both the mitochondrial-Ca2+ fluorescence intensity and the expression of the IP3R-VDAC-MCU complex in MPP+-induced neuronal cells. Additionally, it significantly decreased the levels of ROS, the decline in MMP, and apoptosis rates in these cells.Discussion and conclusionThe findings provide novel insights into the potential of CRSJG in treating neuronal loss in PD.